2013
DOI: 10.1371/journal.pone.0069243
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Gland Lengths and Iceball Dimensions Predict Micturition Functional Outcome Following Salvage Prostate Cryotherapy in Men with Radiation Recurrent Prostate Cancer

Abstract: IntroductionTissue cryoablation is a potential curative option for solid malignancies, including radiation recurrent prostate cancer (RRPC). Case series of salvage cryotherapy (SCT) in RRPC have reported promising disease free survival (DFS) outcomes and acceptable toxicity profile. While many men receive SCT, no predictive factors for treatment induced side effects are known. The aim of this study is to validate the oncologic outcome of SCT in a large multi-centre patient cohort and to identify potential para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…With regard to adverse events, previous studies of cryotherapy and ADT have found that short-term adverse events have very little effect on overall/long-term quality of life; 37 however, they may incur considerable additional costs in patient treatment, so it is important to capture any cost or quality of life impacts of any acute adverse events and how these may impact on model outcomes. Therefore, the model allowed for patients in the SC cohort to experience the seven most common SC-related adverse events (incontinence, retention, lower urinary tract symptoms, perineal pain, haematuria, urethra stricture and fistula), utilising the worst case estimates reported in recent literature 22 33 35 to ensure the base-case analysis was pessimistic towards cryotherapy. Persistent erectile dysfunction would be experienced by the majority of patients who have RRPC before undertaking cryotherapy or beginning ADT, as a result of prior treatment, 6 which is accounted for in the baseline utility level for all cohorts (as detailed in online supplementary material ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to adverse events, previous studies of cryotherapy and ADT have found that short-term adverse events have very little effect on overall/long-term quality of life; 37 however, they may incur considerable additional costs in patient treatment, so it is important to capture any cost or quality of life impacts of any acute adverse events and how these may impact on model outcomes. Therefore, the model allowed for patients in the SC cohort to experience the seven most common SC-related adverse events (incontinence, retention, lower urinary tract symptoms, perineal pain, haematuria, urethra stricture and fistula), utilising the worst case estimates reported in recent literature 22 33 35 to ensure the base-case analysis was pessimistic towards cryotherapy. Persistent erectile dysfunction would be experienced by the majority of patients who have RRPC before undertaking cryotherapy or beginning ADT, as a result of prior treatment, 6 which is accounted for in the baseline utility level for all cohorts (as detailed in online supplementary material ).…”
Section: Discussionmentioning
confidence: 99%
“…6–8 The Markov model comprises four states: ‘pre-ADT’ which for post-SC patients is biochemical disease-free survival (BDFS), ‘BDFS with ongoing ADT’, ‘Progression’ and ‘Death’. Cryotherapy-associated adverse events (urinary incontinence, obstructive urinary symptoms/retention, lower urinary tract symptoms, perineal pain, haematuria, urethral stricture and fistula) will typically manifest within 3 months post-treatment, 22 and are assigned an additional cost and quality of life decrement for this time period. Patients with troublesome ADT-induced hot flushes may require additional antiandrogen treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent Finley et al study analyzed up-to-date oncologic and functional outcomes, as well as complications of salvage cryotherapy for radiationrecurrent prostate cancer and reported 21.7% urinary incontinence rate [18]. Other new study reported even better results: long term incontinence rate was 12% (using 1 pad per day beyond 6 months post-salvage cryotherapy) and fistula rate of 1.8% [19].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Ahmad and colleagues (CROP trial) in their cohort of 283 patients reported an incontinence rate of 12% (0-1 pad/ day). 22 In our experience we found a higher rate of mild-moderate incontinence (≤1 pad/day) 49%, 31% and 3% in Groups 1, 2 and 3, respectively; for severe incontinence (>2 pad/ day), we reported a similar rate (1.5% , 5% and 3%) for Groups 1, 2 and 3, respectively. Pisters and colleagues reported in a comparable sized series 4.4 % (defined as incontinence requiring use of pads), which is commensurate with our results.…”
Section: Discussionmentioning
confidence: 99%